The transformation of the ﬁgure of Wizimir in Renaissance chronicles (the lost chronicle of Wapowski, the chronicles of the Bielski) - Żurek, Agnieszka (Melusine. Old Literature and Culture, 2024)
In the mid-16th century, within the already crystallized set of legendary rulers of Poland preceding Mieszko I, a new ﬁgure emerges – Wizimir, the son of Lech, victorious in the war against Denmark. He ﬁrst appears in the now lost chronicle of Bernard Wapowski, of which we have partial knowledge from accounts by Marcin Bielski and Marcin Kromer. The source is the chronicle of Saxo Grammaticus, as evidenced by both Kromer’s marginal notes and direct quotes from the Danish chronicler. The story of Wizimir easily took root in the early modern chronicle tradition because the progressive elimination of mythical ahistorical ele- ments from history deprived them, particularly, of glorious victories. Wizimir’s wars against the Danes ﬁll this gap, additionally reﬂecting in the realm of mythical history the dream of dominance over the Baltic.